2018
DOI: 10.1177/0361198118799169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Traffic Impacts of Mass Evacuation of Halifax: Flood Risk and Dynamic Traffic Microsimulation Modeling

Abstract: This paper presents a comprehensive evaluation of traffic impacts of a mass evacuation of the Halifax Peninsula under several flooding scenarios. Flood extent and associated damages to the transport network are identified through digital elevation modeling that intersects with the Halifax stream and transport networks. The resulting flood scenarios inform a traffic microsimulation model that uses a dynamic traffic assignment-based microsimulation approach and simulates the evacuation of 34,808 evacuees estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…It was found that vehicles’ departure rate of every exit is mainly dependent on the time headway of the background traffic flows on the road connecting the exit of the parking lot. We also know that the dynamic distribution of background traffic flows in the evacuation road network influences the optimal evacuation routes greatly; this observation is in line with the study of Alam et al [49]. Additionally, to our knowledge, the method proposed in this research is an optimization model with minimum evacuation time, which is also applicable in the vehicle evacuation problems of other infrastructures, e.g., tunnels and bridges.…”
Section: Discussionsupporting
confidence: 83%
“…It was found that vehicles’ departure rate of every exit is mainly dependent on the time headway of the background traffic flows on the road connecting the exit of the parking lot. We also know that the dynamic distribution of background traffic flows in the evacuation road network influences the optimal evacuation routes greatly; this observation is in line with the study of Alam et al [49]. Additionally, to our knowledge, the method proposed in this research is an optimization model with minimum evacuation time, which is also applicable in the vehicle evacuation problems of other infrastructures, e.g., tunnels and bridges.…”
Section: Discussionsupporting
confidence: 83%
“…There is considerable marine movement through Halifax Harbor, located alongside the peninsula. Furthermore, Halifax is on a hurricane path that has previously caused devastation, as demonstrated in Alam et al (15). In 2003, Hurricane Juan made landfall in the Halifax Regional Municipality, causing eight fatalities.…”
Section: Context and Problem Statementmentioning
confidence: 98%
“…. To obtain the zonal clearance time, a microsimulation model developed by Alam et al is updated and utilized to simulate evacuation scenarios (24). The ''clearance time'' required to evacuate each zone on the Peninsula is determined through the simulation.…”
Section: Estimation Of the Mobility Vulnerability Variables Through Evacuation Microsimulation Modelingmentioning
confidence: 99%
“…These studies combined activity-based models with traffic simulation models. One of the current authors’ earlier contributions also developed a sequential modeling framework that includes a flood risk model, a regional transport network model, and a traffic microsimulation model ( 24 ). However, vulnerability assessment requests the distribution of population in different time periods, which is absent within these sequential evacuation modeling frameworks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation